Genologia wobec rewolucji cyfrowej. Przypadek reportażu - Pietrzak, Przemysław (Tematy i Konteksty, 2022)
I compare the concept of today intermedial reportage to that before Internet era. Several features of this genre, usually considered as purely contemporary ones, can be found in the works of 20th century Polish writers including interwar period. Multi-, trans- and intermedial reportages, multiplication of their editorial channels and some forms of participation can be discovered before time of World Wide Web, on condition that we take into consideration newspaper editions, not only those in the books. Digital revolution then looks merely like a change of carrier rather than a huge turn in the history of some literary genres. Moreover, what it offers (internet channels, social media), is of much less durability than traditional paper texts, and readers’ participation here is frequently limited to commentaries or some cues for authors. Many of them vanish shortly afterwards, what makes a ‘participatory culture’ a cultural illusion.